Hydroxamate siderophore production by opportunistic and systemic fungal pathogens. - Holzberg, M (1983)
It has been suggested that siderophores may function as virulence factors. There have been few studies on production of siderophores by opportunistic and pathogenic fungi. We examined siderophore production by Absidia corymbifera, Aspergillus niger, Rhizopus arrhizus, Rhizopus oryzae, Blastomyces dermatitidis, Histoplasma capsulatum, Sporothrix schenickii, Candida albicans, and Trichophyton mentagrophytes. Fungi were cultured at 37 and 27 degrees C in a chemically defined low-iron media (0.2 microM Fe). Culture supernatants were assayed for siderophores by two nonspecific methods [FeCl3 and Fe(ClO4)3] and three chemically specific assays (catechol, 2,3-dihydroxybenzoate, and hydroxamate). All fungi secreted siderophores. Only siderophores of the hydroxamate type were found. More siderophore was produced at 27 degrees C than at 37 degrees C. The present study adds eight fungi to the list of known siderophore producers and confirms siderophore production by H. capsulatum.